Screening siRNAs against host glycosylation pathways to develop novel antiviral agents against hepatitis B virus. Issue 10 (24th August 2020) - Ito, Kiyoaki; Angata, Kiyohiko; Kuno, Atsushi; Okumura, Akinori; Sakamoto, Kazumasa; Inoue, Rieko; Morita, Naoko; Watashi, Koichi; Wakita, Takaji; Tanaka, Yasuhito; Sugiyama, Masaya; Mizokami, Masashi; et al.
Abstract : Aim: Hepatitis B virus (HBV) relies on glycosylation for crucial functions, such as entry into host cells, proteolytic processing and protein trafficking. The aim of this study was to identify candidate molecules for the development of novel antiviral agents against HBV using an siRNA screening system targeting the host glycosylation pathway. Methods: HepG2.2.15.7 cells that consistently produce HBV were employed for our in vitro study. We investigated the effects of siRNAs that target 88 different host glycogenes on hepatitis B surface antigen (HBsAg) and HBV DNA secretion using the siRNA screening system. Results: We identified four glycogenes that reduced HBsAg and/or HBV DNA secretion; however, the observed results for two of them may be due to siRNA off‐target effects. Knocking down ST8SIA3, a member of the sialyltransferase family, significantly reduced both HBsAg and HBV DNA secretion. Knocking down GALNT7, which transfers N ‐acetylgalactosamine to initiate O ‐linked glycosylation in the Golgi apparatus, also significantly reduced both HBsAg and HBV DNA levels. Conclusions: These results showed that knocking down the ST8SIA3 and GALNT7 glycogenes inhibited HBsAg and HBV DNA secretion in HepG2.2.15.7 cells, indicating that the host glycosylation pathway is important for the HBV life cycle and could be a potential target for the development of novel anti‐HBV agents.